Performance Analysis of Jalan Senawang 2 and Jalan Berlian Intersection, Seremban, Negeri Sembilan: A Case Study - Sum, Winky; David Daniel, Basil (Recent Trends in Civil Engineering and Built Environment, 2024)
Traffic congestions and long queues were always being observed at the signalised intersection of Jalan Senawang 2 and Jalan Berlian, Seremban, Negeri Sembilan. Hence, this study was conducted to analyse the level of service (LOS) of the intersection based on the delays, queue length, and degree of saturation. In addition, this study also aimed to propose suitable improvements for the study location. A pilot study was carried out to observe the intersection and identify the critical peak period of the intersection. The video filming technique was applied to collect most of the required data. The video was recorded on a sunny Tuesday during the evening peak (5.30 p.m. – 7.30 p.m.). SIDRA Intersection 8.0 was employed in this study as a tool to analyse the performance of the intersection. The results showed that the study location has low LOS (LOS E) with long delays (70 s/veh), long queues (179m) and a high degree of saturation (0.98). An improvement was proposed to enhance the performance of the study location, which was adding extra lanes. As a result, the performance of the study location improved from LOS E to LOS C with a reduction in delays, queue lengths and degree of saturation.